2005
DOI: 10.1007/bf03036450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organophosphorus compounds on ATP production and mitochondrial integrity in cultured cells

Abstract: Recent studies in vivo and in vitro suggested that mitochondrial dysfunction follows exposure to organophosphorus (OP) esters. As mitochondrial ATP production is important for cellular integrity, ATP production in the presence of OP neurotoxicants was examined in a human neuronal cell line (SH-SY5Y neuroblastoma cells) and primary dorsal root ganglia (DRG) cells isolated from chick embryos and subsequently cultured to achieve maturation with axons. These cell culture systems were chosen to evaluate toxic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
2
29
0
1
Order By: Relevance
“…Augmented ROS production causes defects in the mitochondrial genome, leading to impaired oxidative phosphorylation, which not only limits ATP generation but also further promotes ROS production [49,50]. Previous works demonstrated an increase in superoxide production due to the inhibition of the respiratory chain complex I after organophosphorus exposure [51]. Moreover, the complex I is the primary source of ROS in a variety of pathological processes [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…Augmented ROS production causes defects in the mitochondrial genome, leading to impaired oxidative phosphorylation, which not only limits ATP generation but also further promotes ROS production [49,50]. Previous works demonstrated an increase in superoxide production due to the inhibition of the respiratory chain complex I after organophosphorus exposure [51]. Moreover, the complex I is the primary source of ROS in a variety of pathological processes [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that Me-Pa impairs sperm mitochondrion during their transit through the epididymis. Recent studies suggest that mitochondrion is an important early target for OP compounds resulting in altered ATP production and mitochondrial integrity in cultured neuronal cells (Massicotte et al, 2005). The lack of an effect on MMP at 28 dpt may be due to the fact that structural modifications of many organelles including mitochondria occur during spermatogenesis (Meinhardt et al, 1999); therefore, any change, such as decreased MMP, caused at earlier stages on the testis may not be present at the end of the epididymal maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Since, there are limited data about the hepatotoxicity of OPs in humans, it is not certain whether changes in biochemical parameters indicate actual liver damage. (90)(91)(92)(93)(94), energy production (93,(95)(96)(97), and cell death (98)(99)(100). Several studies have found an association between mitochondrial dynamics and malathion-induced drop in mitochondrial ATP synthesis in rat liver (9) or quinalphos and acephate effects on liver succinic dehydrogenase (84,85,101) and ATPase activities (87) -all of them the key enzymes for oxidative phosphorylation.…”
Section: Biochemical Evidence Of Op Hepatotoxicitymentioning
confidence: 99%